Role of tocotrienol in reproductive system: a systematic review - Mohd Yusof, Siti Raihana (2016)
In nature, vitamin E have been found to be present in eight isomers which are a-,β-,y- and 8-tocopherol and a-,β-,y- and 8-tocotrienol. This research was conducted on the role of tocotrienol in reproductive system. 48 articles (human, animal and cell culture studies) were identified through Pubmed and EMBASE database searches and examination of review articles. The abundance studies of tocopherol (TP) had left behind the precious value of tocotrienol (T3) as the powerful and potent anti-oxidant. Besides, both also plays their roles in other activities such as anti-cancer, anti-angiogenic and anti-inflammatory in reproductive system but in different circumstances. Present study included the history of vitamin E, sources of T3, structure of T3 isomers and the role of T3 in mammalian reproductive system. Limited study of the effects of T3 in reproductive system suggest that more studies should be implemented.